Coronary artery disease in the military patient. Issue 3 (5th August 2015) - Parsons, Iain; White, S; Gill, R; Gray, H H; Rees, P
Abstract : Ischaemic heart disease is the most common cause of sudden death in the UK, and the most common cardiac cause of medical discharge from the Armed Forces. This paper reviews current evidence pertaining to the diagnosis and management of coronary artery disease from a military perspective, encompassing stable angina and acute coronary syndromes. Emphasis is placed on the limitations inherent in the management of acute coronary syndromes in the deployed environment. Occupational issues affecting patients with coronary artery disease are reviewed. Consideration is also given to the potential for coronary artery disease screening in the military, and the management of modifiable cardiovascular disease risk factors, to help decrease the prevalence of coronary artery disease in the military population.